1988
DOI: 10.1111/j.1751-1097.1988.tb02877.x
|View full text |Cite
|
Sign up to set email alerts
|

Response Differences Between Two Soybean Cultivars With Contrasting Uv‐b Radiation Sensitivities

Abstract: Soybeans (Glycine ma.r [L.] Merr. cvs. Essex and Williams) were grown in an unshaded greenhouse under two levels of biologically effective ultraviolet-B (UV-B,,,) radiation (effective daily dose: 0 and l1.S kJ m->) for 34 days. Ultraviolet-B radiation reduced leaf area and total plant mass in Essex but these parameters were unaffected in Williams. Differences in both anatomical and biochemical characteristics were found between cultivars. Some of these differences were inherently distinct between cultivars wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 22 publications
1
37
0
Order By: Relevance
“…An increase in leaf thickness as a response to u.v. radiation has been documented previously (Murali & Teramura, 1986;Murali, Teramura & Randall, 1988;Cen & Bornman, 1990Bornman & Vogelmann, 1991), as well as a decrease (Staxen & Bornman, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…An increase in leaf thickness as a response to u.v. radiation has been documented previously (Murali & Teramura, 1986;Murali, Teramura & Randall, 1988;Cen & Bornman, 1990Bornman & Vogelmann, 1991), as well as a decrease (Staxen & Bornman, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…It is also possible that measures of only total activities of enzymes may not adequately reflect UV-induced compartment-specific changes or enzyme alterations that do not change total activity. For example, UV-B could differently regulate enzyme isoforms as reported for POD (Murali et al, 1988) The non-enzymatic defense system consists of low molecular weight antioxidants such as proline, ascorbate, glutathione, α-tocopherol, and carotenoids (Larson, 1988 Rao and Ormord, 1995). However, in maize seedling, UV-B exposure had no effect on the AsA content (Carletti et al, 2003).…”
Section: The Antioxidant Defense Systemmentioning
confidence: 99%
“…Intraspecific differences in the composition and concentration of flavonoids have been found among five cultivars of Cucumis sativus (Murali and Teramura, 1986) and in two cultivars of soybean (Murali et al, 1988), 20 cultivars of wheat , 10 soybean cultivars (Feng et al, 2001), and 20 soybean cultivars (Li et al, 2002). Screening of the total flavonoid contents in 20 Chinese soybean cultivars in a field study using UV-B lamps revealed that seven cultivars had increased total flavonoid levels while five showed decreased levels, and no changes were observed in eight cultivars (Zu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the course of evolution, natural selection led to the development of species capable of tolerating a higher UV-B level in locations where this was an ecological advantage. Many authors have investigated the effect of increased UV-B radiation on the morphological, ultrastructural, photochemical, biochemical and physiological parameters of various crops under field and greenhouse conditions, including peas (Strid et al, 1990), wheat (Teramura, 1980), soya (Teramura and Caldwell, 1981;Murali et al, 1988;Kramer et al, 1992), sugar beet (Bornman et al, 1983), turnip rape (Demchik and Day, 1996), beans (Cen and Bornman, 1990) and marrow (Sisson, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…In the course of evolution, natural selection led to the development of species capable of tolerating a higher UV-B level in locations where this was an ecological advantage. Many authors have investigated the effect of increased UV-B radiation on the morphological, ultrastructural, photochemical, biochemical and physiological parameters of various crops under field and greenhouse conditions, including peas (Strid et al, 1990), wheat (Teramura, 1980), soya (Teramura and Caldwell, 1981;Murali et al, 1988;Kramer et al, 1992), sugar beet (Bornman et al, 1983), turnip rape (Demchik and Day, 1996), beans (Cen and Bornman, 1990) and marrow (Sisson, 1981).Very few papers are to be found, however, in which the experimental plant is maize, one of the world's most important crops. Investigations on the effect of increased UV-B radiation were reported by Hart et al (1975) and Santos et al (1998) on the duration of maize flowering, Pfahler (1981) on the germination ability of pollen and the growth of the pollen tube, Vu et al (1982) and Santos et al (1990) on the accumulation of carbohydrates, and Basiouny et al (1978) and Santos et al (1993) on the quantities of leaf chlorophyll and total soluble protein.…”
mentioning
confidence: 99%